Cerámica Reforzada con Fibras de Alúmina; Material para Aplicación en la Construcción - Hernández Moreno, Silverio (Acta Universitaria, 2006)
This article presents a case of study in which a new composite material was developed in the laboratory containing a ceramic base material, and it is reinforced with alumina fi bers, which are also derived from ceramic materials. This study began with a development of a method toselect and to evaluate building materials, thus the method is important part in the study of the development of this new material. It was decided to call this ceramic material Reforcer®, because it has been reinforced with ceramic alumina fi bers, which improves several properties of the traditional ceramics, like mechanic, thermal and acoustical properties, therefore, this material can be used in special and diverse applications in the building construction industry in Mexico.